2022
DOI: 10.1007/s42010-022-00153-y
|View full text |Cite
|
Sign up to set email alerts
|

“Gendered differences versus doing gender”: a systematic review on the role of gender in CSCL

Abstract: Gender equity in education is an essential UN sustainable development goal. However, it is unclear what aspects of gender are important to consider in regard to research outcomes as well as how findings can be interpreted in the context of gender stereotypes and bias. This lack of clarity is particularly salient in the STEM field. Computer-supported collaborative learning (CSCL) is a group learning method where learners work together on group tasks that aim at the sharing and co-construction of knowledge. Asid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Viswambaran and Diwakar (2021) showed that it is highly effective to promote social norms of gender equity and inclusion among students by discussing everyday examples in group discussions. In light of this, a systematic literature review by Kube et al (2022) showed that CSCL, as a has the potential to create more gender-inclusive learning environments in STEM. However, they found more research is needed to explore the social and psychological mechanisms of inclusion in a CSCL-based intervention regarding gender bias.…”
Section: Computer-supported Collaborative Learning (Cscl)mentioning
confidence: 99%
See 1 more Smart Citation
“…Viswambaran and Diwakar (2021) showed that it is highly effective to promote social norms of gender equity and inclusion among students by discussing everyday examples in group discussions. In light of this, a systematic literature review by Kube et al (2022) showed that CSCL, as a has the potential to create more gender-inclusive learning environments in STEM. However, they found more research is needed to explore the social and psychological mechanisms of inclusion in a CSCL-based intervention regarding gender bias.…”
Section: Computer-supported Collaborative Learning (Cscl)mentioning
confidence: 99%
“…It further serves as a validation and complement of existing literature on gendersensitive pedagogies by transferring it to CSCL environments (cf. Kube et al, 2022). Lastly, involving women teachers in the development of gender-sensitive pedagogies with the goal of promoting inclusivity and diversity in STEM education is a source of empowerment and agency for women working, teaching and studying in STEM that stimulates further commitment.…”
Section: Present Researchmentioning
confidence: 99%
“…Nevertheless, the study field choice is not student-gender neutral as men and women tend to significantly differ in terms of their preferences and enrolments per different academic specializations [6][7][8][9]. More precisely, men are more prone to choose science, technology, engineering, and mathematics, whereas women show a higher probability of choosing arts, humanities, and social sciences, or medicine [10][11][12][13][14][15][16][17]. Although women are a majority among the high-education enrolled students at a global level, field study segregation remains a critical factor that accounts for the prevalence of wage inequalities among men and women in the labor market [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the academic literature mainly analyzed domestic college students' gendered preferences for fields of study [10,11]. Nevertheless, research on international students might deliver valuable opportunities for understanding how gender and broader contextual factors impact the academic choices of persons educated in different socioeconomic and cultural milieux from their country of origin.…”
Section: Introductionmentioning
confidence: 99%
“…CSCL, which aims at knowledge sharing and co-construction [7], is a teamwork method of technical support. It involves meaningful interaction with others based on common goals and ultimately improves social skills and the ability to comprehensively use the information for innovation.…”
Section: Introductionmentioning
confidence: 99%